Female infertility - Bhattacharya, Siladitya (BMJ Publishing Group, 2010)
INTRODUCTION: About 17% of couples in industrialised countries seek help for infertility, which may be caused by ovulatory failure, tubal damage or endometriosis, or a low sperm count. In developed countries, 80% to 90% of couples attempting to conceive are successful after 1 year and 95% after 2 years. METHODS AND OUTCOMES: We conducted a systematic review and aimed to answer the following clinical questions: What are the effects of treatments for infertility caused by ovulation disorders? What are the effects of treatments for tubal infertility? What are the effects of treatments for infertility associated with endometriosis? What are the effects of treatments for unexplained infertility? We searched: Medline, Embase, The Cochrane Library, and other important databases up to October 2009 (Clinical Evidence reviews are updated periodically, please check our website for the most up-to-date version of this review). We included harms alerts from relevant organisations such as the US Food and Drug Administration (FDA) and the UK Medicines and Healthcare products Regulatory Agency (MHRA). RESULTS: We found 55 systematic reviews, RCTs, or observational studies that met our inclusion criteria. We performed a GRADE evaluation of the quality of evidence for interventions. CONCLUSIONS: In this systematic review we present information relating to the effectiveness and safety of the following interventions: clomifene; drug-induced ovarian suppression; gonadotrophin priming of oocytes before in vitro maturation; gonadotrophins; gonadotrophin-releasing hormone agonists plus gonadotrophins; gonadotrophin-releasing hormone antagonists; in vitro fertilisation; intrauterine insemination alone, or combined with gonadotrophins or clomifene; laparoscopic ablation of endometrial deposits; laparoscopic ovarian drilling; laparoscopic removal; metformin; ovarian wedge biopsy; pulsatile gonadotrophin-releasing hormone; selective salpingography plus tubal catheterisation; tamoxifen; tubal flushing; and tubal surgery before in vitro fertilisation.